“Estandarización de un protocolo de expansión ex vivo de células progenitoras hematopoyéticas aisladas de sangre de cordón umbilical en co-cultivo con células madre mesenquimales de diferentes tejidos” (2022)
Umbilical cord blood is used as a source of hematopoietic progenitor cells, for regeneration of the hemopoietic and immune systems in various hematological diseases; despite that, a low cellular dose limits its application in pediatric patients. In this st udy the standardization of cell expansion technique of compensation for the dose infused cells is proposed, through ex vivo manipulation of hematopoietic progenitor cells from umbilical cord blood before transplantation. The expansion model was performed b y coculture with mesenchymal stem cells and bone marrow fetal tissues unexplored. The results show that the mesenchymal stem cells coculture studied allowed to maximize cell dose of hematopoietic progenitor cells between 5 and 16 folds, with high potenti al clonogenic. Moreover, evidence that treatment with gamma irradiation maintains the capacity to support hematopoietic mesenchymal stem cells from the three sources studied regarding the treatments without irradiation, promoting conditions in the ex vivo expansion system in coculture. It is expected that this standardized protocol will contribute to the development of ex vivo expansion larger scale, towards enabling its clinical use and expand further application in adults.